Pharmacology is the Backbone of Rational Prescribing - Prof. Mainul Haque (Journal of Applied Pharmaceutical Science, 2017)
No abstract is available, please download PDF to read the full-text article.
Keywords: Pharmacology, Rational Prescribing, Medicines, Therapeutics.